Mutilating Purpura Fulminans in an Adult with Meningococcal Sepsis - Arnáiz-García, María Elena; Arnáiz-García, Ana María; Gutierrez-Diez, Francisco; Nistal, Juan Francisco; González-Santos, Jose María; Pulitani, Ivana; Amado-Diago, Carlos; Arnáiz, Javier (Puerto Rico Health Sciences Journal, 2017)
We report a dramatic case of meningococcal sepsis manifesting as purpura fulminans in an elderly diabetic woman. Hemodynamic instability and severe bilateral cutaneous lesions involving her hands and feet developed rapidly. Specific antibiotic therapy and the administration of inotropic and vasopressor drugs were initiated. The severity and extension of the cutaneous lesions (attributed to purpura fulminans) worsened because of the need for vasoconstrictors for the treatment of septic shock. Bilateral transmetatarsal and metacarpal amputations were required to stabilize the patient.